Pass completion rate and match outcome at the World Cup in Brazil in 2014 - Krol, M.; Konefal, M.; Chmura, P.; Andrzejewski, M.; Zajac, A.; Chmura, J. (Polish Journal of Sport and Tourism, 2017)
Introduction. Having possession of the ball makes it possible for the players of a team to undertake a greater number of actions that can help the team win the match. The aim of the current study was to determine the number and completion rate of passes made from different distances in relation to percentage ball possession and the outcome of the match in the group stage of the FIFA World Cup held in Brazil in 2014. Material and methods. The study included 32 teams who participated in the final tournament. The performance of 266 players (682 observations) who played 48 matches in the group stage was examined. Only players who took part in the entire match were included in the research, and goal-keepers were excluded. The data used in the study, which had been recorded by means of the Castrol Performance Index system, were obtained from the FIFA official website. The total number of passes and the percentage of completed passes were analysed, which were classified as short, medium, and long, in relation to the team`s percentage possession of the ball (over and below 50%) and the outcome of the match (win, loss, or draw). Results. Out of the three types of passes which were examined in the study, teams playing in the World Cup in Brazil most often made medium passes. The number of these passes was the highest in matches won. These matches were also characterised by a significantly higher percentage of completed long passes. Conclusions. Players from teams who were in possession of the ball more than 50% of the time performed a higher number of all types of passes, regardless of the outcome of the match. The completion rate for these players was significantly higher only for short and medium passes.